2015
DOI: 10.1155/2015/649568
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritigenin Protects Rats from Carbon Tetrachloride Induced Hepatic Injury through PGC-1αPathway

Abstract: The lack of effective treatment for liver cirrhosis and hepatocellular carcinomas imposes serious challenges to the healthcare system. Here, we investigated the efficacy and mechanism of liquiritigenin involved in preventing or retarding the progression of liver diseases in a rat model with chronic carbon tetrachloride (CCl4) exposure. Sprague Dawley rats were given CCl4 and lliquiritigenin alone or simultaneously for 8 weeks before liver was harvested to check histological changes by Hematoxylin and Eosin (H&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…In the present study, CCl 4 treatment reduced the level of PGC1α, as shown previously in models of liver injury[34,35]. Treatment with serelaxin, or the combination of serelaxin and rosiglitazone, restored PGC1α levels.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, CCl 4 treatment reduced the level of PGC1α, as shown previously in models of liver injury[34,35]. Treatment with serelaxin, or the combination of serelaxin and rosiglitazone, restored PGC1α levels.…”
Section: Discussionsupporting
confidence: 91%
“…A widely-accepted assumption is that the reactive oxygen species (ROS) are the main causes of CCl 4 -induced acute liver injury. Therefore, anti-oxidative therapy is an effective means of preventing and attenuating oxidative stress-related liver diseases ( 27 ). Antioxidant enzymes, such as SOD, perform important functions in defense mechanisms against the harmful effects of ROS and free radicals in biological systems.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of such substances aims to improve quality of life, increase survival, slow disease progression, and, possibly, mitigate the damage caused by formation of ROS and free radicals (FRs)[8,9]. …”
Section: Introductionmentioning
confidence: 99%